Self Esteem Viewed Assertive Behaviour Of Students SMA Parulian 1 Medan - evawaty hutapea (Jurnal Psikologi Universitas HKBP Nommensen, 2020)
This study aimed to determine the relationship between assertive behavior and self esteem. The hypothesis proposed that there is a positive relationship between assertive behavior and self esteem, assuming that the higher is assertive behavior, the higher self esteem and vice versa. The subjects were 152 students of SMA PARULIAN 1 Medan. Data were obtained from a scale for measuring assertive behavior and self esteem. The calculation was performed by means of testing requirements analysis (assumption) that consists of a test for normality and linearity. Data analyzed by Product Moment analysis through SPSS 18 for windows. Data analyzed by Product Moment analysis through SPSS 18 for windows. The result of data analysis showed that r = 0.489, and p = 0.000 (p < 0.05). The results of this study indicated that the contribution (R2) of the assertive behavior variable on the quality of life was at 23.9 %, and the remaining 76.1 % was influenced by other factors not examined in this study. Based on the results, it was concluded that the hypothesis can be accepted. It means there is a positive relationship between assertive behavior and self esteem